Parkinson Hastalarında Algılanan ve Gerçek-Zamanlı Çift-Görev Performansının Farklı Motor-Kognitif Çift-Görev Eşleşmeleri Altında İncelenmesi. - Şanlı, Ali Furkan; Hüseyinsinoğlu, Burcu Ersöz; Bilgiç, Başar; Hanağası, Haşmet Ayhan (Hacettepe University Faculty of Health Sciences Journal)
Objective: In individuals with Parkinson's disease, dual-task difficulties can be assessed either through self-reported perception scales or objective performance-based tests. However, the relationship between these two evaluation methods remains unclear. The aim of this study was to examine the association between perceived and actual dual-task performance in individuals with Parkinson's disease and to evaluate performance differences across various types of dual-task conditions. Methods: A total of 117 participants diagnosed with idiopathic Parkinson's disease, classified between Hoehn and Yahr stages 1 to 3, with a Mini-Mental State Examination score of at least 21 and no history of dementia, were included. Actual dual-task performance was assessed using the Timed Up and Go test with additional motor and cognitive secondary tasks, as well as the Six Spot Step Test. Perceived dual-task performance was measured using the Dual-Task Questionnaire. Statistical analyses were performed using Spearman's correlation coefficient and the Friedman test. Results: The mean age of the participants was 62.44 ± 10.06 years, and the average disease duration was 6.34 ± 4.69 years. A statistically significant but weak correlation was found between perceived performance and the cognitive dual-task condition of the Timed Up and Go test (r=0.214; p=0.02), as well as the motor dual-task condition (r=0.277; p=0.002). No significant relationship was observed between perceived performance and the Six Spot Step Test (r=0.165; p=0.075). Additionally, the dual-task cost in the motor condition of the Timed Up and Go test was significantly higher than that in the cognitive condition (Z= -4.4; p<0.001). Conclusion: The weak association between perceived and real-time dual-task performance suggests that these two domains should be evaluated separately. Furthermore, the type of secondary task accompanying the walking task may lead to different outcomes in individuals' dual-task performance. A detailed examination of these effects in patients with Parkinson's disease could provide valuable guidance for developing more effective rehabilitation plans.